The Effect of Current Ratio, Debt to Equity Ratio, Return on Assets, And Earning Per Share on Stock Price of Conventional Taxi and Bus Companies Listed In Indonesia Stock Exchange In Period of 2013-2017 - Sari, Novita; Astini, Rina (International Humanities and Applied Science Journal, 2020)
This study aims to examine and analyze the effect of current ratio, debt to equity ratio, returnon assets and earning per share on the stock price. The object of this study is conventional taxi and bus companies in Indonesia Stock Exchange on 2013-2017. The sample selection is using purposive sampling and got six companies that match the criteria. The method used is panel data regression analysis and found that the appropriate model to use is a common effect. From the result of this study obtained the variable of earning per share has a positive and significant effect on the stock price.